Decision Support Systems Application to Business Processes at Enterprises in Russia - Aksyonov, Konstantin; Bykov, Eugene; Dorosinskiy, Leonid; Smoliy, Elena; Aksyonova, Olga; Antonova, Anna; Spitsina, Irina (IntechOpen, 2011)
None